Pengaruh Harga, Promosi Dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Jasa Pada Khanza Dry N Wash Tanjung Morawa, Kab. Deli Serdang - Ramadhany, Dean Tiara; Radiansyah, Muhammad (Universitas Muhammadiyah Metro, 2022)
This study analyzes the effect of price, promotion and service quality on the decision to use Khanza Dry N Wash services in Tanjung Morawa, Kab. Deli Serdang. The research method used in this research is descriptive quantitative. This research was conducted in Hamlet II Jl. Tirta Deli No. 90 A Tanjung Morawa. The time of this research began in January 2022 until March 2022. The population in this study were consumers of Khanza Dry n Wash Tanjung Morawa, amounting to 1,110 people. The results of using the slovin formula in this study the researchers took a sample of 92 consumers of Khanza Dry n Wash Tanjung Morawa. The analytical method used is the multiple linear regression method using the SPSS program. The results of this study indicate that the value of t-count > t-table (2.955 > 1.29114) and a significant value of 0.004 is less than 0.1, meaning that the price has a significant effect on the decision to use the services of Khanza Dry n Wash Tanjung Morawa, then Ha1 is accepted. The value of t-count > t-table (3.157 > 1.29114) and a significant value of 0.002 less than 0.1 means that promotion has a significant effect on the decision to use the services of Khanza Dry n Wash Tanjung Morawa, then Ha2 is accepted. The value of t-count > t-table 5.544 > 1.29114) and a significant value of 0.000 is smaller than 0.01, meaning that service quality has a significant effect on the decision to use the services of Khanza Dry n Wash Tanjung Morawa, then Ha3 is accepted. The value of Fcount (43.811) > Ftable (2.76), and a significance value of 0.000 < 0.1, it can be concluded that the fourth hypothesis is accepted, meaning that Price (X1), Promotion (X2), and Service Quality (X3) variables affect simultaneously (simultaneously) on the Decision to Use Services (Y). The adjusted coefficient of determination (R Square) is 0.639, this means that 63.9% of the dependent variable can be explained by the independent variable while the rest (100% - 63.9% = 36.1%) is explained by other variables outside the variables studied